2006
DOI: 10.1002/ejoc.200500816
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Saponins with Cholestanol, Cholesterol, and Friedelanol as Aglycones

Abstract: Procedures for the synthesis of branched Xylβ(1→3)[Galβ(1→2)]‐Glc and Xylβ(1→3)[Galβ(1→2)]‐GlcUA trisaccharides β‐linked to the 3‐O of cholesterol, cholestanol, and friedelanol, respectively, were developed. To this end, β‐selective glucosylation of cholesterol with glucosyl donors giving selective access to 2‐O, 3‐O, and 6‐O was studied. This way intermediates 10 and 21 having 2‐O‐acyl, 3‐O‐benzyl and 4,6‐O‐benzylidene or also benzyl protection were obtained. Removal of the 2‐O‐acyl group and then galactosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…The 2a-O-galactosylation could therefore be carried out immediately, and the desired trisaccharide 8 was obtained in practically quantitative yield with galactosyl donor 7 [33] under IP conditions, even though access to the 2a-OH group would be anticipated to be sterically hindered. The 1 H NMR spectroscopic data for 8 and also for the next compound indicate the presence of a 1 C 4 h 4 C 1 conformational equilibration of the xylopyranosyl residue, as was also observed previously; [25] however, the 13 C NMR spectroscopic data clearly indicate the generation of the β-anomer. For the transformation of the glucosyl residue into a glucuronic acid residue, the 4a,6a-Obenzylidene group was removed with ethyl mercaptan as nucleophile in the presence of p-toluenesulfonic acid (TsOH) as catalyst; [34] subsequent oxidation of the 4a,6a-O-unprotected intermediate with tetramethylpiperidine Noxide (TEMPO)/sodium hypochlorite (NaOCl) [35,36] resulted in clean oxidation of the primary hydroxy group to furnish the uronic acid derivative 9, which could be structurally fully assigned.…”
Section: Synthesis Of Allobetulin-based Saponinsupporting
confidence: 58%
See 3 more Smart Citations
“…The 2a-O-galactosylation could therefore be carried out immediately, and the desired trisaccharide 8 was obtained in practically quantitative yield with galactosyl donor 7 [33] under IP conditions, even though access to the 2a-OH group would be anticipated to be sterically hindered. The 1 H NMR spectroscopic data for 8 and also for the next compound indicate the presence of a 1 C 4 h 4 C 1 conformational equilibration of the xylopyranosyl residue, as was also observed previously; [25] however, the 13 C NMR spectroscopic data clearly indicate the generation of the β-anomer. For the transformation of the glucosyl residue into a glucuronic acid residue, the 4a,6a-Obenzylidene group was removed with ethyl mercaptan as nucleophile in the presence of p-toluenesulfonic acid (TsOH) as catalyst; [34] subsequent oxidation of the 4a,6a-O-unprotected intermediate with tetramethylpiperidine Noxide (TEMPO)/sodium hypochlorite (NaOCl) [35,36] resulted in clean oxidation of the primary hydroxy group to furnish the uronic acid derivative 9, which could be structurally fully assigned.…”
Section: Synthesis Of Allobetulin-based Saponinsupporting
confidence: 58%
“…For the 3-O-glycosylation of the aglycones, a linear strategy (i.e., construction of the trisaccharide moiety at the aglycon) was chosen because a convergent strategy (i.e., glycosylation of the aglycon with a preprepared trisaccharide donor [23,26] ) lacking anchimeric assistance in the glycosylation step did not provide satisfactory anomeric selectivities. [23,27] Through this approach, with the help of anchimeric assistance, [25] good glycosylation results were expected. Success in this endeavour should also greatly facilitate the total synthesis of QS 21 and analogues.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As reported in Scheme 2, the benzylic protecting group was selectively removed by Pd/C catalyzed hydrogenation. 24 Different catalyst concentrations and solvents were tested in order to avoid the concomitant hydrogenation of the cholesterol double bond. It was found that 5% of Pd/C in EtOH/CH 2 Cl 2 2/1 provide the best conditions, affording after 24 h the desired product 5 in 92% overall yield.…”
mentioning
confidence: 99%